Techniques for mining the design of e-government services to enhance end-user experience. (18th November 2008) - Panagis, Yiannis; Sakkopoulos, Evangelos; Tsakalidis, Athanasios; Tzimas, Giannis; Sirmakessis, Spiros; Lytras, Miltiadis
The World Wide Web solutions are increasingly endorsed by several levels of government in order to deliver all kinds of the so-called e-government services. To face the complexity of joint design and development procedures, it is imperative to adopt a web modelling language such as the WebML. In this work, we propose a methodology that enhances the ability to detect, during the early development stages, similar design snippets that perform the same functionalities. Additionally, a methodology to infer frequent constructs at the design level, when applied to similar e-government services, can lead to safe conclusions as for when a specific construct constitutes a design pattern. Finally, we illustrate a validation scenario.